Ilmu Hikmah dalam Pandangan Masyarakat Bojonegara - sholahuddin al Ayubi; Irma Suryaningsih (Aqlania, 2021)
he Bojonegara community is a modern society, but in their daily life, especially in Pengarengan Village, there are still some people who use the powers of “Ilmu hikmah” which are believed to be able to realize various desires or various life problems. The Pengarengan community uses this method to achieve certain goals. “Ilmu hikmah” in the view of the people of Bojonegara has a very strong appeal in various ways. So that the society has high expectations to believe in “Ilmu hikmah”. The study used a descriptive analysis method and it combinated library research and field research, namely collecting data obtained from the field using observation, interview, and documentation techniques. The results show that the trust held by the people of Bojonegara in the “Ilmu hikmah” is very high, however, in this belief there are several practices of "Ilmu hikmah" that are not in accordance with Islamic teachings.